Analisis Strategi Pemasaran Media Sosial Usaha Jasa Percetakan CV. Mitra Abadi Sablon Solo - Danang Suparwanto; Muhammad Syihabbudin (PT. Karya Inovatif Nusantara, 2026)
This study aims to analyze the marketing strategy of CV. Mitra Abadi Sablon, a printing service company focusing on plastic cup screen printing in Surakarta City. The research employs a case study method with a descriptive qualitative approach. The main data sources consist of promotional activities, in-depth interviews with the business owner, and relevant literature. Data analysis is conducted using the Miles and Huberman model, which includes data reduction, data display, conclusion drawing, and verification. The findings indicate that the marketing strategy emphasizes product customization based on customer demand, flexible pricing with wholesale schemes for large orders, promotion through word-of-mouth recommendations, and service-oriented distribution. Several challenges are identified, including price competition with large-scale printing platforms, fluctuations in raw material prices, and inconsistent digital promotion activities. This study recommends improving professionalism in digital marketing management, strengthening customer and feedback management, enhancing price transparency, and increasing operational capacity in order to maintain and improve the company’s competitive advantage.